Mathematics

Question

Theo started to solve the quadratic equation (x + 2)^2 – 9 = –5. He added 9 to both sides and the resulting equation was (x + 2)^2 = 4. Next, he took the square root of each side. Which was the resulting equation of that step?
x + 2 = ±4
x + 2 = ±2
x + 2 = ±8
x + 2 = ±16

2 Answer

  • When we take the square root of each side, the equation would become:
    abs (x+2) = 2
    ⇒ x+2 = ±2.

    The final answer is 
    x + 2 = ±2.

    Hope this helps~




  • The square root of  (x + 2)²  is  (x + 2) .

    The square roots of  4  are  +2  and  -2 .

    So the resulting equation was            x + 2  =  ± 2 .

    From there, it was pretty easy for Theo to find the solutions
    to the original equation . . .

    If  (x + 2) = +2 , then  x = 0 .

    If  (x + 2) = -2 , then  x = -4 .